1996
DOI: 10.1073/pnas.93.20.10876
|View full text |Cite
|
Sign up to set email alerts
|

Long-term expression of erythropoietin in the systemic circulation of mice after intramuscular injection of a plasmid DNA vector.

Abstract: Erythropoietin (Epo)-responsive anemia is a common and debilitating complication ofchronic renal failure and human immunodeficiency virus infection. Current therapy for this condition involves repeated intravenous or subcutaneous injections of recombinant Epo. In this report, we describe the development of a novel muscle-based gene transfer approach that produces long-term expression of physiologically significant levels of Epo in the systemic circulation of mice. We have constructed a plasmid expression vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(93 citation statements)
references
References 25 publications
3
89
1
Order By: Relevance
“…11,[16][17][18][19][20][21] Plasmid DNA delivered directly to muscle generally results in persistent albeit low-level gene expression since skeletal muscle takes up, episomally maintains and expresses plasmid DNA for a time notably longer than other tissues. 12,25,[40][41][42] Furthermore, this method of gene delivery circumvents some of the problems encountered with viral vectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,[16][17][18][19][20][21] Plasmid DNA delivered directly to muscle generally results in persistent albeit low-level gene expression since skeletal muscle takes up, episomally maintains and expresses plasmid DNA for a time notably longer than other tissues. 12,25,[40][41][42] Furthermore, this method of gene delivery circumvents some of the problems encountered with viral vectors.…”
Section: Discussionmentioning
confidence: 99%
“…15 Nevertheless, secretion in blood plasma and/or systemic biological activity of the transgene have been confirmed after i.m. delivery of plasmid vectors encoding for erythropoietin, 16 factor VII, 17 rat kallikrein-binding protein (RKBP), 18 vascular endothelial growth factor (VEGF), 19 interleukin 10, 20 and interferon-␥ receptor/IgG1 fusion protein. 21 These studies suggest that i.m.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of plasmid backbones containing different promoters have been tested for transgene expression in skeletal muscle with varying success. The most widely used are viral promoters, such as cytomegalovirus (CMV) immediate-early promoter, 28 simian virus, SV40 early promoter 29 and Rous sarcoma virus promoter. 1 These promoters can drive expression in a wide range of cells and tissues eg CMV promoter can be activated in nearly all cell types.…”
Section: Promoter Enhancer and Other Elementsmentioning
confidence: 99%
“…In addition, plasmid DNA vectors are easier to construct, can accept large cDNA inserts, and can be prepared as pure chemical solutions without the risk of contamination with wild-type infectious particles. [33][34][35] It has been reported that the delivery of heterologous genes into skeletal muscle can provide the sustained production of proteins in the circulation. 18 Intramuscular injection of plasmid DNA encoding interferon-␣ or endostatin has showed the inhibition of tumor growth.…”
Section: Was Apparently Inhibited In the Treatment With Psectag2b-vasmentioning
confidence: 99%